Juridical Analysis of Government Policies on Ownership of Rights to Flats: (Research Study In Kampung Utama, Batam City) - Sisilia Sisilia; Soerya Respationo; Markus Gunawan; Erniyanti Erniyanti (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
The policy of ownership of the right to the flats is an important aspect in the arrangement of vertical housing in Indonesia, especially in dense urban areas such as Kampung Utama Batam City. The background of this research focuses on the complexity of ownership dualism between individual property rights over units and collective rights to common parts, common objects, and common land. Conflicts of interest and management problems often arise, hindering the optimal implementation of policies. The purpose of this study is to analyze the implementation of government policies on ownership of rights to apartment units in Kampung Utama Batam City, identify existing obstacles, and provide recommendations for improvement. The research method used is a normative juridical approach with case studies. Data was collected through analysis of legal documents, interviews with stakeholders, and field observations. The analysis was carried out using positive legal theory from John Austin to understand the existing legal framework, legal system theory from Lawrence M. Friedman to evaluate the interaction between legal structure, substance, and culture, and legal certainty theory from Sudikno Mertokusumo to assess the clarity and predictability of applicable laws. The results of the study show that although the policy has been well drafted in Law No. 20 of 2011 concerning Flats, its implementation in the field still faces various obstacles. Dualism of ownership, unclear certificate status, complex administrative procedures, and lack of legal socialization are some of the main problems found. Strengthening the role of the Flats Owners and Occupants Association (P3SRS), the use of digital technology for administrative procedures, and increased supervision and law enforcement were identified as solutions to overcome these obstacles. The suggestions provided include increased coordination between related agencies, active community participation in the management of flats, and simplification of administrative procedures by the government. More effective implementation is expected to provide better legal certainty and create a harmonious residential environment in Kampung Utama Batam City.